Evaluation of the neuroprotective activity of a new allylmorpholine derivative in a rat model of traumatic brain injury - V. A. Prikhodko; A. V. Kan; Yu. I. Sysoev; I. A. Titovich; N. A. Anisimova; S. v Okovityi (Разработка и регистрация лекарственных средств, 2021)
Introduction. The search for and development of new drugs capable of reducing the severity of neurological deficit in traumatic brain injury are a critical task for investigational pharmacology. Chromone-containing allylmorpholines are a new group of neuroprotective drug candidates that have been shown to inhibit acetylcholinesterase and butyrylcholinesterase, and block N-methyl-D-aspartate receptors in vitro.Aim. This study aimed to evaluate the neuroprotective activity of the allylmorpholine derivative (E)-4-[3-(8-bromo-6-methyl-4-oxo-4H-chromen- 3-yl)-1-cyclohexylallyl]morpholin-4-ium chloride (33b) in vivo using a rat model of traumatic brain injury.Materials and methods. Traumatic brain injury was induced using the controlled cortical impact model. The allylmorpholine derivative was administered intraperitoneally at 1, 10, or 50 mg × kg-1 b.w. at 1 h after trauma induction, and then daily for the next 6 d. The neurological deficit was assessed using the Limb Placing, Open Field, Elevated Plus Maze, Beam Walking, and Cylinder tests.Results and discussion. At all doses administered, the allylmorpholine derivative had no positive effect on the motor function or exploratory behavior following traumatic brain injury. In the Elevated Plus Maze, 10 mg × kg-1 b.w. of the compound further suppressed exploratory behaviour in the injured animals, which appears to be consistent with its sedative properties observed previously in zebrafish.Conclusion. Despite the previously described in vitro affinity of allylmorpholines towards several molecular targets crucial for the pathogenesis of brain trauma and posttraumatic functional recovery, an allylmorpholine derivative had no neuroprotective effect in a rat model of traumatic brain injury in this study. These results further emphasize the importance of in vivo evaluation of potential neuroprotective drug candidates.